Psychosocial profiles influencing healthy dietary behaviors among adolescents in Shandong Province, China: a cross-sectional study - Shi, Ya; Fu, Lin; Li, Shengping; Jiang, Ke; Shi, Zumin; Sharma, Manoj; Zhao, Yong (Frontiers in Nutrition, 2024)
We aimed to identify the influence of psychosocial profiles on dietary behaviors among school adolescents in China.A cross-sectional study was conducted among 7862 adolescents in 100 schools in Shangdong China. Psychosocial profiles and dietary behavior were assessed using junior high school students' psychosocial profiles questionnaire (JPPQ) and Chinese Diet Quality Questionnaire (DQQ), respectively. Linear regression models were used to investigate the association between adolescents' psychosocial profiles and dietary behaviors.The mean age of the participants was 13.18 ± 1.15, with 48.5% being male, the majority (97.90%) were Han Chinese, and approximately half of the participants (50.90%) resided in rural areas. After adjusting for socio-demographic characteristics, family computer and Internet ownership and usage, healthy dietary behavior was positively correlated with the higher psychosocial profiles score(P<0.05). Stratified analysis results revealed that the highest psychosocial profiles score group was associated with an increased overall global dietary reference (GDR) score in "households without a family computer and Internet" (: 5.357, 95% Cl: 4.931-5.784, P<0.05).Conclusions: Good psychosocial profiles exerted a positive influence on healthy dietary behaviors.Policymakers should focus on Internet usage to maximize the positive effects on global youth health behaviors.